2021
DOI: 10.1155/2021/8870461
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder: Investigating Predictive Adaptive Behavior Skill Deficits in Young Children

Abstract: Autism spectrum disorder (ASD) is a lifelong neurodevelopmental disorder that consists of difficulties with social communication and language, as well as the presence of restricted and repetitive behaviors. These deficits tend to present in early childhood and usually lead to impairments in functioning across various settings. Moreover, these deficits have been shown to negatively impact adaptive behavior and functioning. Thus, early diagnosis and intervention is vital for future success within this population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Such substantial changes in everyday life are added to the pathological traits that are characteristic of the ASD condition, such as inflexibility and trouble with variation in schedule (Reicher, 2020), with a potential regression of previously acquired socio-cognitive skills (Pearson et al, 2018). As for behavior, ASD-related aggressiveness and stereotypies were worsened by social deprivation (Feige et al, 2021) and changes in routine (Alhuzimi, 2021). Regarding home confinement, parents working from home, owing to a better work-life balance (Ipsen et al, 2021), could support ASD children in mitigating their symptoms (Tokatly Latzer et al, 2021;Zwaigenbaum et al, 2015); however, other studies suggest that the positive effect deteriorated when the lockdown lingered, which increased parents' stress levels (Bozkus-Genc & Sani-Bozkurt, 2022).…”
Section: Lockdown Impact On Preschool Children With Asdmentioning
confidence: 99%
“…Such substantial changes in everyday life are added to the pathological traits that are characteristic of the ASD condition, such as inflexibility and trouble with variation in schedule (Reicher, 2020), with a potential regression of previously acquired socio-cognitive skills (Pearson et al, 2018). As for behavior, ASD-related aggressiveness and stereotypies were worsened by social deprivation (Feige et al, 2021) and changes in routine (Alhuzimi, 2021). Regarding home confinement, parents working from home, owing to a better work-life balance (Ipsen et al, 2021), could support ASD children in mitigating their symptoms (Tokatly Latzer et al, 2021;Zwaigenbaum et al, 2015); however, other studies suggest that the positive effect deteriorated when the lockdown lingered, which increased parents' stress levels (Bozkus-Genc & Sani-Bozkurt, 2022).…”
Section: Lockdown Impact On Preschool Children With Asdmentioning
confidence: 99%
“…Autism Spectrum Disorder (ASD) is defined as a lifelong neurodevelopment disorder in children characterized by deficiencies in social communication and interaction, along with limited interest, repetitive behavior, and sensory issues (Lord et al, 2020;Feige et al, 2021). Lord et al (2020) added that ASD could also be shown from several levels of intellectual deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorderitself is a lifelong neurodevelopmental disorder that occurs in early childhood and is characterized by deficits in communication and social interaction, restricted interests, repetitive behaviors, and sensory problems (Grant, 2019;Lord et al, 2020;Feige, Mattingly, Pitts, & Smith, 2021). This disorder has a significant impact on the quality of personal and family life (Emily & Grace, 2015).…”
Section: Introductionmentioning
confidence: 99%